Menumbuhkan Nilai Karakter Anak melalui Film Anak Ruby Rainbow di Kelas II MI Gampong Meutia Langsa - restela, rika; Megawati, Putri (azkiya, 2023)
Animated films have the advantage of being an alternative learning medium that instills character values in children. The ideal criteria for animated films include ease of understanding, simplicity, effective storytelling, the use of polite language, entertainment through engaging games, and the delivery of values easily accepted by children. One animated film that meets these criteria is "Ruby Rainbow". The aim of this research is to identify the character values present in the children's film "Ruby Rainbow" and evaluate its ability to foster character values in the second-grade students of MI Gampong Mutia Langsa. This qualitative research employs a study design involving 26 students as research subjects during the first semester of the academic year 2022/2023. Research instruments include observation sheets, interviews, and documentation. The research analysis reveals that in the "Ruby Rainbow" season 2, particularly in episodes 11 "Penyanyi" and " Ling Ling menetaskan telur," episode 38 "Kota Sekapal Danau Pelangi (Part 2)," and episode 50 "Tidak ada pasien yang sabar," produced by 38°C Animation Studio and CJ E&M Corporation, there are character values such as hard work, social concern, creativity, appreciation of achievements, communication skills, and responsibility.